A service evaluation exploring clients' experiences of being on a waiting list for individual psychological therapy with a community learning disability team. - Hall, Laura (British Journal of Learning Disabilities, 2024)
Background: Service user involvement is imperative in the delivery of mental health services. However, a paucity of research has explored how individuals with a learning disability find waiting for therapy. Therefore, this project aimed to explore how service users accessing a community learning disability team experienced waiting for psychological therapy. Methods: Ten adults on a waiting list for psychological therapy in Yorkshire, UK completed a semistructured interview, which explored their experiences of being on the waiting list. Interviews were transcribed and analysed using thematic analysis. Findings: Five superordinate themes were drawn from the analysis. Participants recalled long waits for therapy, struggled waiting and were unsure when therapy would start. Relief and hopefulness were common when they were put forward for therapy. Difficulties reading and/or remembering letters were prominent. Keeping busy and support from others helped participants cope while waiting. Participants would have valued additional support including having someone on call, regular check‐ins and information on other appropriate services. Conclusions: This project led to a range of recommendations to inform a psychology waiting list standard operating procedure, service developments and improve the waiting list experience for service users. A future project exploring parent and carer experiences of the waiting list is warranted. Accessible summary: This project looked at the experiences of people with a learning disability when on a waiting list for psychological therapy with a community learning disability team.Ten adults on the waiting list for psychological therapy were interviewed and asked about their experiences.Most participants said that they had a long wait for therapy. Most people found waiting hard.Participants were relieved when they found out they were going to get help.This project led to recommendations to help improve the service.